Prevalence and associated factors of Smokeless Tobacco (SLT) use among adolescents in Indonesia: GYTS 2019 data analysis - Syamsuriansyah Syamsuriansyah; Salman Salman; Heni Rusmitasari; Marlynda Happy Nurmalita Sari; Maretalinia Maretalinia (Public Health of Indonesia)
Background: Smokeless tobacco (SLT) use is a new trend since the banning of smoking in many public places, including among adolescents. Many people believe that SLT is a harmful reduction method compared to cigarettes. However, there are many risks of using the SLT, such as Head and neck cancer (HNC), cancer of the mouth, and coronary heart disease.